Disruptive behavior scale for adolescents (DISBA): development and psychometric properties - Mahmood Karimy; Ahmad Fakhri; Esmaeel Vali; Farzaneh Vali; Feliciano H. Veiga; L. A. R. Stein; Marzieh Araban (BMC, 2018)
Abstract Background Growing evidence indicates that if disruptive behavior is left unidentified and untreated, a significant proportion of these problems will persist and may develop into problems linked with delinquency, substance abuse, and violence. Research is needed to develop valid and reliable measures of disruptive behavior to assist recognition and impact of treatments on disruptive behavior. The aim of this study was to develop and evaluate the psychometric properties of a scale for disruptive behavior in adolescents. Methods Six hundred high school students (50% girls), ages ranged 15-18 years old, selected through multi stage random sampling. Psychometrics of the disruptive behavior scale for adolescents (DISBA) (Persian version) was assessed through content validity, explanatory factor analysis (EFA) using Varimax rotation and confirmatory factor analysis (CFA). The reliability of this scale was assessed via internal consistency and test-retest reliability. Results EFA revealed four factors accounting for 59% of observed variance. The final 29-item scale contained four factors: (1) aggressive school behavior, (2) classroom defiant behavior, (3) unimportance of school, and (4) defiance to school authorities. Furthermore, CFA produced a sufficient Goodness of Fit Index > 0.90. Test-retest and internal consistency reliabilities were acceptable at 0.85 and 0.89, respectively. Conclusions The findings from this study suggest that the Iranian version of DISBA questionnaire has content validity. Further studies are needed to evaluate stronger psychometric properties for DISBA.